The Liquidity Premium: Evidence from the UK - Chen, Hongjie Desmond (2009)
The literature review covers the discussion of various asset pricing models such as the Capital Asset Pricing Model, the 3 –Factor Model and the APT as well as their empirical evidences and conjectures in their abilities and inabilities to capture anomalies.